2013
DOI: 10.1111/add.12359
|View full text |Cite
|
Sign up to set email alerts
|

Did hardening occur among smokers in England from 2000 to 2010?

Abstract: Aims To assess trends in the prevalence of ‘hardcore’ smoking in England between 2000 and 2010, and to examine associations between hardcore smoking and socio-demographic variables.Design Secondary analysis of data from the United Kingdom's General Lifestyle Survey (GLF) and the Health Survey for England (HSE).Setting Households in England.Participants Self-reported adult current smokers resident in England aged 26 years and over.Measurements Hardcore smokers were defined in three ways: smokers who do not want… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…Jarvis et al 25 estimated that in the mid-1990s the percentage of hardcore smokers in England was 16%, defined as daily smokers in the previous 5 years, without quit attempts in the past 12 months, and without desire or intention to quit. Also, for England between 2000 and 2010, Docherty et al 26 suggest that hardening might have been occurring because the proportion of smokers with low motivation to quit and high degree of dependence increased, with an average of about 13% of smokers identified as hardcore smokers during this time. Even accepting these estimates, however, shows that the ‘hardcore’ is a small fraction of all smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Jarvis et al 25 estimated that in the mid-1990s the percentage of hardcore smokers in England was 16%, defined as daily smokers in the previous 5 years, without quit attempts in the past 12 months, and without desire or intention to quit. Also, for England between 2000 and 2010, Docherty et al 26 suggest that hardening might have been occurring because the proportion of smokers with low motivation to quit and high degree of dependence increased, with an average of about 13% of smokers identified as hardcore smokers during this time. Even accepting these estimates, however, shows that the ‘hardcore’ is a small fraction of all smokers.…”
Section: Discussionmentioning
confidence: 99%
“…As we discussed in our papers and in our Table 1 [2], there are no accepted definitions of these terms (and we believe it would be good to have agreement on them). In our paper, we used hardcore smokers as one measure of assessing hardening, as has been conducted in various other studies, which we cited in the paper.…”
mentioning
confidence: 88%
“…We suggested that the slight increase in smokers with higher dependence and low motivation to quit between 2006 and 2009 may be due to the introduction of smoke-free laws in England in 2007 [2]. Despite substantial support for smoke-free laws there are some who oppose it, and one recent study using data from the United States suggested that there are some smokers who become more comfortable with their behaviour (and therefore less likely to quit) now that a smoke-free law is in place due to smoking behaviour affecting non-smokers to a much lesser extent [3].…”
mentioning
confidence: 96%
“…Docherty et al [1] examined whether or not the proportion of hardcore smokers in England increased from 2000 to 2010 by using three different definitions-high nicotine dependence, lack of desire to quit, and a combination of both factors. The authors found no significant time trends in dependence or desire to quit, but found a modest increase in the proportion of smokers who met both criteria from 2006 to 2009, a trend that remained after controlling for socio-demographic factors.…”
Section: Hardcore Smoking Does Not Necessarily Indicate Hardeningmentioning
confidence: 99%
“…Further, the paper by Docherty et al [1] appears to use the terms 'hardcore smokers' and 'hardening' interchangeably, but they are not synonymous. Viewed as a potential indicator of a need for new tobacco control strategies, hardening is defined as a decline in a country's smoking prevalence accompanied by that nation's overall smoking population becoming on average more unwilling to, or incapable of, quitting [3].…”
Section: Hardcore Smoking Does Not Necessarily Indicate Hardeningmentioning
confidence: 99%